Biphasic pattern of histone gene expression during Drosophila oogenesis. - Ruddell, A.; Jacobs-Lorena, M. (Proceedings of the National Academy of Sciences of the United States of America, 1985)
The expression of histone genes during Drosophila oogenesis was compared to periods of DNA synthesis as well as to the pattern of actin gene expression. Accumulation of histone mRNAs was measured by RNA blot hybridization. Relatively low levels of histone mRNAs are present in egg chambers prior to stage 10, during the period of nurse and follicle cell polyploidization. Surprisingly, histone mRNAs accumulate rapidly and selectively after stage 10, coinciding with the onset of nurse cell degeneration and well after DNA synthesis and actin mRNA accumulation have ceased. A large proportion of the histone mRNAs is associated with polysomes at all times, indicating that expression of histone genes is not strictly coupled to DNA synthesis. The burst of histone mRNA accumulation near the end of oogenesis may provide a store of maternal histone mRNA to support the rapid cleavages that occur during early embryogenesis. These and previous results suggest that genes are independently regulated during differentiation of the Drosophila egg chamber.